The counterfeit agent - Berenson, Alex. (New York : G.P. Putnams Sons, 2014)
"A suspense novel featuring former CIA agent John Wells, by the author of THE SHADOW PATROL and THE NIGHT RANGER"--
Keywords: Intelligence officers -- Fiction; Undercover operations -- Fiction; Suspense fiction; Spy stories